Diffusion of a Peer-Led Suicide Preventive Intervention Through School-Based Student Peer and Adult Networks - Pickering, Trevor A.; Wyman, Peter A.; Schmeelk-Cone, Karen; Hartley, Chelsey; Valente, Thomas W.; Pisani, Anthony R.; Rulison, Kelly L.; Brown, Charles Hendricks; LoMurray, Mark (Frontiers in Psychiatry, 2018)
Background: Peer-led interventions have been applied to prevent various health behavior problems and may be an important complement to individual-level suicide prevention approaches. Sources of Strength trains student "peer leaders" in secondary schools to conduct prevention activities that encourage other students to build healthy social bonds and strengthen help-seeking norms. Prior work examining diffusion of peer-led programs has focused on youths’ closeness to peer leaders but minimally on other factors such as connections to adults and suicidal behavior. Methods: We examined implementation and dissemination of Sources of Strength in 20 schools. Over one year 533 students were trained as peer leaders and 3,730 9th-12th graders completed baseline surveys assessing friendships and adults at school, and suicidal thoughts/behaviors; and end-of-year surveys reporting intervention exposure: viewed poster/video, attended presentation, direct peer communication, and activity participation. Chi-square tests compared exposure rates by student and network characteristics. Multi-level logistic regression models tested predictors of exposure across individual and school-level characteristics. Results: Exposure to the intervention varied greatly by school and by individual student characteristics and network position. Training more peer leaders increased school-wide exposure for all modalities except presentation (Bs 0.06-0.10, p’s<.05). In multivariate models, exposure was consistently higher for students closer to peer leaders in the friendship network (ORs 1.13-1.54, p’s<.05) and students who named more trusted adults (ORs 1.08-1.16, p’s<.001); and lower for males (ORs 0.56-0.83, p’s<.05). In multivariate models, training more students as peer leaders predicted exposure to poster-video and direct peer communication in larger schools (OR=3.34 and 2.87, respectively). Network characteristics influenced exposure similarly for students with suicidal thoughts and behaviors. Discussion: Our findings confirm prior work showing the importance of personal affiliations to peer leaders and natural networks as a medium for diffusion of peer-led prevention efforts. We build on that work by showing independent effects of closeness to adults at school and number of peer leaders trained. There is a need to strategically select peer leaders to maximize closeness to students school-wide, particularly in larger schools. Additional work is required for Sources of Strength to devise messaging strategies to engage males and students isolated from adults at school.